KKNI-BASED CURRICULUM PROGRAM EVALUATION IN FEBI, STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA MEDAN - Syafaruddin Syafaruddin; Amiruddin Siahaan; Suasana Nikmat Ginting (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This paper aims to analyze the evaluation of the KKNI-based curriculum program at the Faculty of Islamic Economics and Business (FEBI) UIN North Sumatra Medan. The curriculum evaluation model used is the CIPP model (Context, Input, Process, Product). This study used a qualitative approach, then data was obtained through observation, interviews, questionnaires, and documentation techniques as well as various sources. The results of this study indicate that (1) Context, from this aspect, FEBI UIN North Sumatra Medan applies an KKNI-based curriculum referring to Presidential Regulation No. 8 of 2012; (2) Inputs, including lecturer's RPS, quizzes, assignments, learning participation, mid-semester exams and end-semester exams; (3) Process, including monitoring of internal quality assurance units at the FEBI and university levels at UIN North Sumatra Medan, as well as external quality assurance in the context of institutional and study program accreditation; (4) Product, through formative evaluation (such as group assignments, quizzes, individual assignments, exams) and empirical evaluation (behavior and student participation in the learning process).